Produksi Benih Kentang Sistem Aeroponik dan Root Zone Cooling dengan Pembedaan Tekanan Pompa di Dataran Rendah - Sumarni, Eni; Sudarmaji, Arief; Suhardiyanto, Herry; Saptomo, dan Satyanto Krido (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2016)
ABSTRACTNutrition pumps pressure is important in aeroponic. Optimal pump pressure produces well oxygenation, so that increases the dissolved oxygen content in the nutrition. It is good for plant roots. The purpose of this study was to determine pump pressure on the growth and yield potato seeds grown in aeroponics in lowland 125 m asl with root zone cooling. This study used a randomized block design non factorial. Data were analyzed using analysis of variance followed by a further test of orthogonal contrasts at the level of α = 5%. Results showed that different pump pressure on the provision of nutrient, temperature cooling in the root zone gave different results on the number of potato tubers per plant and weight per tuber in each variety. Root zone cooling temperature 15 °C, the pump pressure> 1.5 atm produce highest number of tubers per plant, i.e. 11.8 tuber of Granola variety and 8.2 tuber of Atlantic variety. The was no tuber produced from control (without referigeration). The highest weights per tuber (10.35 and 5.01 g for Atlantic and Granola variety, respectively) were reached with cooling temperature at 15 °C and the pump pressure > 1.5 atm.Keywords: evaporative cooling, hydroponics, potato, tuber, variety